New Headway. Upper-Intermediate: Teacher's Resource Book - Cooke J. Joanna; Hudson J. Jane; Soars L. Liz; Soars J. John (New York, Oxford University Press, 2006)
New Headway Upper-IntermediateThe world's most trusted English course New Headway is the course teachers and learners can rely on. Why? An authoritative integrated syllabus, motivating topics, and clearly focused tasks combine with a real understanding of what works in the classroom. It all makes for effective teaching and effective learning.Tried and tested all over the world, it's probably the most popular course ever written! of Ne sate? Up-to-date topics and texts with global appeal I Listening passages with wide-ranging examples of authentic English NEW Spoken English sections extend grammar presentations to cover informal phrases NEW Music of English boxes highlight stress and intonation patterns in the Everyday English sections.